Anxiety and Parenting Style in Children and Adolescents With Tic Disorders - Wattanarojjanakit P. (2023)
Background: To study the associations of parenting styles and anxiety in Thai children and adolescents with tic disorders, comparing with healthy children and adolescents. Methods: A cross-sectional study of children and adolescents aged between six and 18 years with tic disorders were enrolled. The control group comprised gender- and age-matched healthy children with no history of tic disorders. The Yale Global Tic Severity Scale was used to assess tics severity. All participants were evaluated for anxiety trait and state using the State-Trait Anxiety Inventory for Children (STAIC). The anxiety disorders were screened by using the Screen for Child Anxiety-Related Emotional Disorders questionnaire. Parenting styles were evaluated by the Parenting Styles and Dimensions Questionnaire. Results: A total of 41 children with tic disorders and 41 children in the control group were enrolled. According to the STAIC, the anxiety state and trait scores were significantly higher in the tic disorders group than in the control group (median [interquartile range]: 28 [13 to 31] vs 8 [6 to 10], P≤0.001, and 31 [18 to 36] vs 8 [3 to 11], P≤0.001, respectively). Furthermore, anxiety disorder was more frequently found in children with tic disorders than in controls (58.5% vs 17.1%, P≤0.001). There was no significant correlation between anxiety symptoms, parenting styles, and the severity of tics. Conclusion: Anxiety is common in Thai children with tic disorders. Screening for anxiety in children and adolescents with tic disorders is essential, leading to early detection and providing proper management.